The Study for Saving Energy and Optimization of LED Street Light Heat Sink Design - Chi-Chang Hsieh; Yan-Huei Li (Advances in Materials Science and Engineering)
LED lamps are characterized by high energy efficiency, high luminance, and long lifespans. However, the heat radiation problem caused by the extra high power shortens the lifespan and reduces the luminous efficiency of such lamps. This study introduced the development of a novel cooling fin structure for LED lamps and compared its performance with those of commercially available products. The objective of the design was to reduce the maximum temperature and temperature difference on the fin, the amount of aluminum required for fin manufacturing, and CO2 emissions to save energy. The study employed the Taguchi method for experiment planning and used gray relational analysis and principal component analysis to determine the optimal parameter combination for cooling fins. The results showed that the maximum temperature on the fin surface dropped by 2.62°C in environments without forced convection, which indicated improved lighting efficiency. Furthermore, the amount of aluminum used per unit volume for fins was reduced by 15%, which effectively reduced CO2 emissions during the manufacturing process.